Perempuan Dalam Budaya Patriarki: Kajian Karya Sastra Penulis Perempuan Indonesia - Sari, Seplia Sartika; Hayati, Yenni (Institut Teknologi Pendidikan Indonesia, 2023)
Patriarchal culture raises various problems in women's lives to cause physical and mentalsuffering. Gender injustice experienced by women is one proof of the strength of patriarchal values. The female authors show these things in literary works to voice resistance in an effort to obtain equal rights between men and women. The problems of women described by female authorstend to show marginalization, discrimination and subordination of women as a form of genderinjustice due to the strong patriarchal culture in social life. This is reflected in the stereotypesinherent in women as the second class, women and the marriage paradigm, women and careerchoices, and women as objects of sexuality. These criticisms are shown through the way of thinking of the main female leaders who oppose injustice to their gender, and show resistance through actions taken by female leaders in the fabric of stories written by female authors.